2021
DOI: 10.1186/s12877-021-02135-8
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and factors related to urinary incontinence in older adults women worldwide: a comprehensive systematic review and meta-analysis of observational studies

Abstract: Background Urinary incontinence is a common condition in the general population and, in particular, the older adults population, which reduces the quality of life of these people, so this study aims to systematically examine and meta-analyse the overall prevalence of urinary incontinence in older women around the world and the related and influential factors. Methods This report is a comprehensive systematic review and meta-analysis of the findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
2
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 60 publications
8
88
2
11
Order By: Relevance
“…The causes are multifactorial, and the consequences are changes in the quality of life of the population. International systematic review and meta-analysis study indicates prevalence similar to that found in this study (29) . In Brazil, we still do not have precise statistical data in this regard since epidemiological studies are scarce (30) .…”
Section: Discussionsupporting
confidence: 90%
“…The causes are multifactorial, and the consequences are changes in the quality of life of the population. International systematic review and meta-analysis study indicates prevalence similar to that found in this study (29) . In Brazil, we still do not have precise statistical data in this regard since epidemiological studies are scarce (30) .…”
Section: Discussionsupporting
confidence: 90%
“…Banaei and colleagues examined the rate of dyspareunia postpartum 2 . Batmani et al estimated the worldwide prevalence of UI in older women 3 . Lastly, Woodley and colleagues extended their 2020 Cochrane systematic review 4 with a narrative review of pelvic floor training 5…”
Section: Paying Attention To the Pelvic Floor In Pregnancy And Postpartummentioning
confidence: 99%
“…It is estimated that 1 in 4 women aged 18 to 75 years experience UI with the rate increasing with age 6 . Batmani and colleagues estimated the prevalence of UI in those aged 55 to 100 years at 37% 3 . The rates vary by global region with the Americas having the lowest rate at 25.8% and Asia the highest, 45.1% 3 .…”
Section: Paying Attention To the Pelvic Floor In Pregnancy And Postpartummentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary incontinence is a multifarious ailment characterised by involuntary leakage of urine, a global and extensive disorder affecting millions of people worldwide [1]. Urinary incontinence affects women more than men although the accurate prevalence is not known every quarter (25%) out of four person could be affected by urinary incontinence in their life span [2].…”
Section: Introductionmentioning
confidence: 99%